Closed-form solutions for MHD flow of a second-grade fluid through porous space - Khan, M.; Iqbal, Kaleem; Azram, Mohammad (Begell House, Inc. publishers, 2011)

(untitled)
In this paper, closed-form solutions corresponding to the motion of a second-grade fluid through porous space have been established by means of the Laplace transform. The fluid is assumed to be electrically conducting in the presence of a uniform magnetic field and occupies the porous space over an infinite flat plate. Three haracteristic examples are considered: (i) flow due to impulsive motion of the plate, (ii) flow due to the impulsive accelerating plate, and (iii) flow due to the nonuniformly accelerated plate. The analytical results are confirmed numerically by drawing several graphs. The influence of pertinent parameters on flow is delineated. It is noted that the effects of the viscoelastic parameter of the fluid on the flow are much stronger for small values of the viscoelastic parameter as compared with large values of the viscoelastic parameter of the fluid.